IDENTIFIKASI LEVEL KEMAMPUAN BERPIKIR ORISINAL ANAK DALAM STEAM PROJECT BASED LEARNING - Riska Rifani, - (2020)
Penelitian ini dilatarbelakangi oleh tuntutan berbagai kemampuan yang harus dimiliki anak pada abad 21 salah satunya kreativitas. Kreativitas jika dilihat dari ciri-ciri yang berhubungan dengan berpikir kreatif atau kognitif salah satunya kemampuan berpikir orisinal. Dari permasalahan tersebut, salah satu model yang dinilai efektif untuk mengembangkan kemampuan berpikir orisinal, yaitu STEAM Project Based Learning. Model pembelajaran ini dilakukan dengan mengintegrasikan STEAM (Science, Technology, Engeneering, Art and Math), hasil akhirnya menghasilkan produk. Tujuan penelitian ini untuk mendeskripsikan dan mengidentifikasi level kemampuan "berpikir orisinal" siswa pada rangkaian pembelajaran STEAM PjBL I, II, III serta selama rangkaian pembelajaran STEAM PjBL. Metode yang digunakan dalam penelitian ini adalah Mixed Methods model concurrent embedded. Teknik analisis data yang digunakan adalah analisis data kualitatif dan kuantitatif. Hasil penelitian ini menunjukan adanya peningkatan kemampuan berpikir orisinal anak pada setiap rangkaian pembelajaran STEAM Project Based Learning, maka STEAM Project Based Learning diidentifikasi dapat meningkatkan level kemampuan berpikir orisinal anak. This Research is motivated by the demands of various abilities that children must have in the 21st century, one of which is creativity. Talking about creativity, creativity is related to creative thinking when viewed from the characteristics related to the ability to think creatively or cognitively, one of which is the ability to think original. In addition, creativity is contained in KD-2 (Basic Competence-2) which must be developed in children. From these problems, one model that is considered effective for developing original thinking skills, namely STEAM Project Based Learning. This learning model is carried out in groups by integrating STEAM (Science, Technology, Engineering, Art and Math), the end result will produce a product. The purpose of this study was to describe and identify the level of students '"original thinking" ability in the STEAM PjBL I, II and III learning series and to describe and identify the level of students' "original thinking" ability during the STEAM PjBL learning series. The method used in this Research is the Mixed Methods model of concurrent embedded. The data analysis technique used in this Research is qualitative and quantitative data analysis. Qualitative data analysis by analyzing data from the results of observation and documentation, quantitative data analysis using a Likert scale which then converts the data into a percentage. The results of this study indicate an increase in children's original thinking skills in each series of STEAM Project Based Learning learning. So it can be concluded that based on the results of this study, STEAM Project Based Learning was identified to increase the level of children's original thinking skills.